Proposed injury thresholds for concussion in equestrian sports. Issue 3 (March 2020) - Clark, J. Michio; Adanty, Kevin; Post, Andrew; Hoshizaki, T. Blaine; Clissold, Jonathan; McGoldrick, Adrian; Hill, Jerry; Annaidh, Aisling Ni; Gilchrist, Michael D.
Abstract: Objectives: Equestrian helmets are designed to pass certification standards based on linear drop tests onto rigid steel surfaces. However, concussions in equestrian sports occur most commonly when a rider is thrown off a horse and obliquely impacts a compliant surface such as turf or sand. This paper seeks to elucidate the mechanics of such impacts and thereby propose corresponding thresholds for the occurrence of concussion that can improve equestrian helmet standards and designs. Design: The present study examined the biomechanics of real-world equestrian accidents and developed thresholds for the occurrence of concussive injury. Methods: Twenty-five concussive and 25 non-concussive falls in equestrian sports were reconstructed using a combination of video analysis, computational and physical reconstruction methods. These represented male and female accidents from horse racing and the cross-country phase of eventing. Results: The resulting thresholds for concussion [59 g, 2700 rad/s 2, 28 rad/s, 0.24 (MPS), 6.6 kPa and 0.27 (CSMD10 ) for 50% risk] were consistent with those reported in the literature and represent a unique combination of head kinematic thresholds compared to other sports. Current equestrian helmet standards commonly use a threshold of 250 g and a linear drop to a steel anvil resulting in less than 15 ms impacts. This investigation found that concussive equestrian accidents occurred from oblique impacts to turf or sand with lower magnitude and longer duration impacts (<130 g and >20 ms). This suggests that current equestrian helmet standards may not adequately represent real-world concussive impact conditions and, consequently, there is an urgent need to assess the protective capacity of equestrian helmets under real-world conditions.